Origin of Atlantic Sturgeon Collected off the Delaware Coast during Spring Months. (12th January 2015) - Wirgin, Isaac; Breece, Matthew W.; Fox, Dewayne A.; Maceda, Lorraine; Wark, Kevin W.; King, Tim
Abstract: Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus was federally listed under the U.S. Endangered Species Act as five distinct population segments (DPS). Currently, at least 18 estuaries coastwide host spawning populations and the viability of these vary, requiring differing levels of protection. Subadults emigrate from their natal estuaries to marine waters where they are vulnerable to bycatch; one of the major threats to the rebuilding of populations. As a result, identifying the population origin of Atlantic Sturgeon in coastal waters is critical to development of management plans intended to minimize interactions of the most imperiled populations with damaging fisheries. We used mitochondrial DNA control region sequencing and microsatellite DNA analyses to determine the origin of 261 Atlantic Sturgeon collected off the Delaware coast during the spring months. Using individual‐based assignment (IBA) testing and mixed stock analysis, we found that specimens originated from all nine of our reference populations and the five DPSs used in the listing determination. Using IBA, we found that the Hudson River population was the largest contributor (38.3%) to our coastal collection. The James (19.9%) and Delaware (13.8%) river populations, at one time thought to be extirpated or nearly so, were the next largest contributors. The three populations combined in the South Atlantic DPS contributed 21% of specimens; the Altamaha River, the largest population in the South Atlantic DPS, only contributed a single specimen to the collection. While the origin of specimens collected on the Delaware coast was most likely within rivers of the New York Bight DPS (52.1%), specimens that originated elsewhere were also well represented. Genetic analyses provide a robust tool to identify the population origin of individual sturgeon outside of their natal estuaries and to determine the quantitative contributions of individual populations to coastal aggregations that are vulnerable to bycatch and other anthropogenic threats. Received March 17, 2014; accepted September 3, 2014